2014
DOI: 10.3807/josk.2014.18.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Fast Switching of Vertically Aligned Liquid Crystals by Low-Temperature Curing of the Polymer Structure

Abstract: We proposed a method for fast turn-off switching of a vertically-aligned liquid crystal cell by low-temperature curing of the polymer structure. We confirmed that the turn-off times of the fabricated cells were reduced significantly as the curing temperature was lowered to -20℃. We accounted for the effect of low-temperature curing on the turn-off time by using a mathematical model and by observing images obtained via scanning electron microscopy. We also confirmed that low-temperature curing is more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recently it was demonstrated that the response time of LCs at low temperatures can be reduced by forming polymer networks, although their performance needs further improvement [18][19][20][21]. More recently, super-fast-response LCDs over a wide temperature range were demonstrated by continuously applying a vertical-bias electric field to nematic LCs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that the response time of LCs at low temperatures can be reduced by forming polymer networks, although their performance needs further improvement [18][19][20][21]. More recently, super-fast-response LCDs over a wide temperature range were demonstrated by continuously applying a vertical-bias electric field to nematic LCs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%